Strengthening the Social Resilience of Muslim Communities Affected by Flash Floods through the Digitization of Family Archives - Waluyo Satrio Adji; M. Imamul Muttaqin; Didik Wahyudi; Nandia Primasari; Dewi Muliyati (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2026)
The loss of vital family documents during disasters poses significant risks to civil rights, administrative continuity, and community resilience. This study aims to strengthen the social resilience of disaster-affected Muslim communities by digitizing family archives. Conducted in Bumiaji Subdistrict, Batu City, Indonesia, following the 2021 flash flood, this research employed a Participatory Action Research (PAR) approach involving 40 participants. The study collected data through interviews, observations, and document analysis, and analyzed them using descriptive quantitative and thematic qualitative methods. The findings reveal a substantial improvement in participants' archival literacy and digital competencies. Knowledge of family archives increased from 69% to 94.7%, while understanding of digital archiving improved from 42.9% to 78.9%. Participants successfully digitized, organized, and stored essential documents independently, demonstrating enhanced preparedness for disaster risks. The study highlights that digital archiving serves as an effective strategy for preserving civil identity, protecting cultural memory, and ensuring administrative continuity. It further contributes to the discourse on archival studies and disaster management by positioning family-level digital archiving as a practical instrument for strengthening social resilience. This research proposes a replicable community-based model integrating digital literacy, archival preservation, and disaster preparedness, offering policymakers, archival institutions, and disaster-prone communities worldwide valuable insights